PERMAINAN HIGGS DOMINO ISLAND PADA REMAJA (13-15 TAHUN) DI KELURAHAN PEMATANG PUDU KECAMATAN MANDAUDURI (STUDI KASUS PADA ANAK SUKU SAKAI ) - Muhammad Firdaus; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research was conducted in the Pematang Pudu Village with the aim of knowing the things that influence behavior resulting from playing the higgs domino island game and to find out the impact caused by playing the higgs domino island game. This study uses a qualitative descriptive research method. The subjects in this study were 5 teenage informants in the Pematang Pudu Village who actively played the online game higgs domino island. As well as using interview techniques, observation, and documentation. The data sources used consist of primary data and secondary data. The results showed that there were things that influenced the higgs domino online game to occur, namely internal factors, namely lack of activity or boredom, stress or depression, and diversity of choices and external factors, namely the environment of peers and family. As well as having a positive impact, namely online higgs domino game players are addicted because the profits are in the form of money and the negative impacts are addiction, health problems, having debt, lazy to study, irregular sleep patterns. Keywords: Game Online Higgs Domino Island, Factor, Impact